Respuesta :
y - 3x = -8
y = 3x - 8...slope here is 3. A perpendicular line will have a negative reciprocal slope. All that means is " flip " the slope and change the sign. So the slope we need is -1/3.
y = mx + b
slope(m) = -1/3
(3,2)...x = 3 and y = 2
now we sub and find b, the y int
2 = -1/3(3) + b
2 = -1 + b
2 + 1 = b
3 = b
so ur perpendicular equation is : y = -1/3x + 3
y = 3x - 8...slope here is 3. A perpendicular line will have a negative reciprocal slope. All that means is " flip " the slope and change the sign. So the slope we need is -1/3.
y = mx + b
slope(m) = -1/3
(3,2)...x = 3 and y = 2
now we sub and find b, the y int
2 = -1/3(3) + b
2 = -1 + b
2 + 1 = b
3 = b
so ur perpendicular equation is : y = -1/3x + 3
Perpendicular to y - 3x = -8
Change that to slope form
y = 3x - 8
Perpendicular to that means the slopes would equal to -1 when multiplied
3x = -1
Thus the slope of the other equation would be -1/3
y - y1 = m(x - x1)
where m is the slope
y - 2 = -1/3(x - 3)
y - 2 = (-1/3)x - 1
y = (-1/3)x + 1
That's the equation
hope it helps.
Change that to slope form
y = 3x - 8
Perpendicular to that means the slopes would equal to -1 when multiplied
3x = -1
Thus the slope of the other equation would be -1/3
y - y1 = m(x - x1)
where m is the slope
y - 2 = -1/3(x - 3)
y - 2 = (-1/3)x - 1
y = (-1/3)x + 1
That's the equation
hope it helps.